Psychological Capital and Job Satisfaction Among Chinese Residents: A Moderated Mediation of Organizational Identification and Income Level - Zhang, Fang; Liu, Ying; Wei, Tongqi (Frontiers in Psychology, 2021)
The present study examined the mediating effect of psychological capital in the relationship between organizational identification and job satisfaction, and whether the mediation was moderated by income level. 310 Chinese residents were surveyed using the Organizational Identification Scale, Job Satisfaction Scale, Psychological Capital Scale, and a demographic questionnaire. The findings showed a significant positive correlation between organizational identification and job satisfaction of residents, and this relationship was partially mediated by psychological capital. Moreover, income level played a moderating role in the relationship between psychological capital and job satisfaction. Specifically, for residents with less income, their psychological capital influenced their job satisfaction more strongly. The current study contributed to a better understanding of the relationship between organizational identification and job satisfaction. Implications on resident management were discussed.